Advances in electrokinetics and their applications in micro/nano fluidics - Zhao, Cunlu (2013)
Electrokinetic phenomena originally developed in colloid chemistry have drawn great attention in micro- and nano-fluidic lab-on-a-chip systems for manipulation of both liquids and particles. Here we present an overview of advances in electrokinetic phenomena during recent decades and their various applications in micro- and nano-fluidics. The advances in electrokinetics are generally classified into two categories, namely electrokinetics over insulating surfaces and electrokinetics over conducting surfaces. In each category, the phenomena are further grouped according to different physical mechanisms. For each category of electrokinetics, the review begins with basic theories, and followed by their applications in micro- and/or nano-fluidics with highlighted disadvantages and advantages. Finally, the review is ended with suggested directions for the future research.